The impact of paternal alcohol, tobacco, caffeine use and physical activity on offspring mental health: a systematic review and meta-analysis - Kayleigh E. Easey; Gemma C. Sharp (BMC, 2021)
Plain language summary More research has focused on the impact mothers' behaviours (such as smoking or alcohol use) during and around pregnancy may have on their children's health, with less research investigating the role paternal health behaviours may play. This review captured what research was currently available that investigated the impact of paternal alcohol, tobacco, caffeine use, and physical activity during pregnancy on children's mental health. We showed that this area is currently under researched, finding only eight studies. However, of the research that was already published we found evidence of paternal health behaviours having an impact on children's mental health. The strongest evidence was shown for paternal smoking during pregnancy having a negative impact on children's hyperactivity/ADHD. No studies measured paternal caffeine use or physical activity around pregnancy. This review highlights the lack of research that has investigated the association between paternal modifiable health behaviours around pregnancy and offspring mental health. Despite including four different types of paternal health behaviours and a broad definition of offspring mental health across any age, only eight studies were shown. This review suggests further research within this area is needed which may influence health warnings to potential fathers to be both before conception and during pregnancy.